Computational systems biology: from molecular mechanisms to disease - Kriete, Andres; Eils, Roland (Academic Press, 2014)
Introducing Computational Systems Biology Roland Eils and Andres Kriete -- Structural Systems Biology: Modeling Interactions and Networks for Systems Studies Robert B. Russell ... [et al.] -- Understanding Principles of the Dynamic Biochemical Networks of Life Through Systems Biology Hans V. Westerhoff ... [et al.] -- Biological Foundations of Signal Transduction, Systems Biology and Aberrations in Disease Ursula Klingmüller ... [et al.] -- Complexities in Quantitative Systems Analysis of Signaling Networks Christina Kiel and Luis Serrano -- Gene Networks: Estimation, Modeling, and Simulation Seiya Imoto, Hiroshi Matsuno and Satoru Miyano -- Reconstruction of Metabolic Network from Genome Information and its Structural and Functional Analysis Hong-Wu Ma and An-Ping Zeng -- Standards, Platforms, and Applications Stanley Gu and Herbert Sauro -- Databases, Standards, and Modeling Platforms for Systems Biology Juergen Eilsa ... [et al.] -- Computational Models for Circadian Rhythms: Deterministic versus Stochastic Approaches Jean-Christophe Leloup, Didier Gonze and Albert Goldbeter -- Top-Down Dynamical Modeling of Molecular Regulatory Networks Reinhard Laubenbacher and Pedro Mendes -- Discrete Gene Network Models for Understanding Multicellularity and Cell Reprogramming: From Network Structure to Attractor Landscapes Landscape Joseph Xu Zhou ... [et al.] -- Stochastic Simulations of Cellular Processes: From Single Cells to Colonies John Cole ... [et al.] -- Advances in Machine Learning for Processing and Comparison of Metagenomic Data Jean-Luc Bouchot ... [et al.] -- Systems Biology of Infectious Diseases and Vaccines Helder I Nakaya -- Computational Modeling and Simulation of Animal Early Embryogenesis with the MecaGen Platform Julien Delile, René Doursat and Nadine Peyriéras -- Developing a Systems Biology of Aging Andres Kriete and Mathieu Cloutier -- Molecular Correlates of Morphometric Subtypes in Glioblastoma Multiforme Hang Chang ... [et al.] -- Applications in Cancer Research: Mathematical Models of Apoptosis Stefan M. Kallenberger, Stefan Legewie and Roland Eils